Adults With Late Stage 3 Chronic Kidney Disease Are at High Risk for Prevalent Silent Brain Infarction: A Population-Based Study - Chou, Chia-Chi; Lien, Li-Ming; Chen, Wei-Hung; Wu, Mai-Szu; Lin, Shiue-Ming; Chiu, Hou-Chang; Chiou, Hung-Yi; Bai, Chyi-Huey (Stroke (1970), 2011)
The close relationship between stroke and chronic kidney disease (CKD) has been well-documented. However, few studies have focused on silent brain infarction (SBI) in CKD. We investigated the prevalence of SBI in different stages of CKD. We included 1312 participants aged 30 to 93 years who came from either a random sample of residents or from a group of physically examined subjects in the same community. Basic information, clinical evaluations, laboratory tests, and MRI images were assessed. Subjects were divided into groups 1, 2, 3a, and 3b, corresponding to the estimated glomerular filtration rate (eGFR) levels of ≥ 90.0, 60.0 to 89.9, 45.0 to 59.9, and 30.0 to 44.9 mL/min/1.73 m². The crude prevalence was 4.7%: 2.6% (20 of 759 subjects) in group 1; 6.3% (32 of 506) in group 2; 12.9% (4 of 31) in group 3a; and 37.5% (6 of 16) in group 3b (P<0.001). Additionally, SBI also correlated with age, male sex, hypertension, diabetes, moderate carotid plaque, higher blood pressures, obesity, and levels of triglyceride, high-density lipoprotein cholesterol, high-sensitivity C-reactive protein, and uric acid (all P<0.05). The effects for SBI risk in each eGFR group versus group 1 did not increase except for group 3b (OR, 9.34; P<0.001). A close association exists between SBI and eGFR. We have found a significant increase in prevalence of SBI when eGFR is between 30.0 and 44.9 mL/min/1.73 m². Adults with late stage 3 CKD are at high risk for prevalent SBI.